Modelling of the growth and productivity of soy cultivars under irrigation and rainfed conditions (Revista de Ciências Agroveterinárias, 2022)
The aim of this study was to evaluate the fit of semi-empirical models for growth and productivity in soya cultivars under irrigation and rainfed conditions in the state of Alagoas. Two experiments were conducted, the first during the dry season from 14/11/18 to 03/04/19 (140 days), and the second during the rainy season from 20/06/19 to 28/10/19 (130 days) in the coastal-tableland region of Alagoas. The experimental design was of randomised blocks, with the treatments comprising six cultivars of different maturity groups and growth habits (M 6210, M 6410, BMX-Potência, AS 3730, M 8349 and BRS-9383). The following were evaluated: plant height, dry matter and leaf area index (LAI). The sigmoidal and pic log-normal logistic models showed a significant statistical fit (p
Keywords: growth habit; empirical models; Glycine max. (L.) Merrill; soybeans; dry season